Exploring Gynecologists/Obstetricians and General Practitioners’ Perspectives on Sexual Health Management among Obstetric Patients: Insights from a National Portuguese Survey - Kristina Hundarova; Raquel Sousa; Bárbara Laranjeiro; Teresa Bombas; Maria João Carvalho; Sofia Franco (Clinical and Experimental Obstetrics & Gynecology)
Background: Sexual health (SH) remains a marginalized topic in medical education, posing a challenge to healthcare professionals in providing adequate sexual care. This study aimed to assess the knowledge, clinical experience, training experiences and needs of doctors working in Gynecology/Obstetrics (G/O) and General Practice (GP) regarding sexuality during pregnancy. Methods: A cross-sectional study was conducted from September 2022 to March 2023, inviting Portuguese physicians (G/O and GP) to complete an online questionnaire. Results: Of 366 physicians (50.8% GP; 49.2% G/O) surveyed, the majority were female (85.5%), aged between 24 and 35 years (57.9%) and specialists (56.8%). Nearly all respondents (99.2%) recognized the importance of SH during pregnancy, with 86.6% agreeing that inquiring about sexuality is essential, given that 99.2% believe that pregnancy affects SH. However, despite 66.9% of physicians acknowledging that pregnant value sexuality, 55.2% reported that fewer than 10% pose questions, and only 27.6% of doctors inquire about sexuality. Although 85.0% of the respondents felt completely or partially comfortable discussing sexuality, only 24.6% considered themselves skilled to provide SH counselling, with less than a fifth feeling capable of treating specific sexual dysfunctions. The main difficulties were time constraints (75.7%) and lack of training (70.2%), particularly evident in the GP group. More than a quarter of GP responders and 11% of G/O physicians admitted the lack of education or training in this area. Nearly all responders expressed interest in improving their knowledge, with residency training being the most preferred option. Conclusions: Portuguese physicians recognize the importance of sexuality during pregnancy, but only a minority routinely inquire about it during appointments, referring lack of time and training as the major barriers. The study highlights significant deficiencies in Portuguese GP and G/O practitioners concerning sexual health, emphasizing the urgent need for further training in this area.